Multifunctional phototheranostic agent ZnO@Ag for anti-infection through photothermal/photodynamic therapy - Obeng, Enoch; Feng, Jiayao; Wang, Danyan; Zheng, Dongyang; Xiang, Bailin; Shen, Jianliang (Frontiers in Chemistry, 2022)
To overcome the limitations of traditional therapeutics, nanotechnology has presented a synergistic therapeutic approach for the treatment of bacterial infection and biofilms which has widely attracted attention. Herein, we report on a ZnO@Ag nanocomposite with good biocompatibility synthesized by doping ZnO NPs with silver nanoparticles (Ag NPs). ZnO@Ag nanocomposites was synthesized with varying ratios of Ag NPs (0.5%, 2%, 8%). However, under the same experimental conditions, ZnO@8%Ag exhibited outstanding properties compared to the other nanocomposites and the pristine ZnO NPs. ZnO@8%Ag demonstrated excellent photothermal and photodynamic properties. Also, ZnO@8%Ag demonstrated over 99 % inhibition of Staphylococcus aureus (S. aureus) under photothermal therapy (PTT) or photodynamics therapy (PDT) treatment as a result of the excessive generations of ROS by the Ag+ released, while the pristine ZnO showed an insignificant inhibition rate compared to the PBS group (Control). Furthermore, ZnO@8%Ag completely disrupted S. aureus biofilm under a combined PTT/PDT treatment, a synergetic trimodal therapy, the molecular mechanism of biofilm inhibition remains unclear. Hence the excellent photothermal, photodynamic, biocompatibility and bactericidal properties of ZnO@8%Ag present it as an appropriate platform for bacterial and biofilm treatment or other biomedically related applications.